Effectiveness of radioiodine therapy with 131I-metaiodobenzylguanidine (131I-MIBG) for the treatment of neuroblastoma (Research, Society and Development, 2023)
Objective: To assess whether radioiodine therapy with 131I-metaiodobenzylguanidine (131I-mIBG) increases the survival of patients diagnosed with neuroblastoma, avid-mIBG, refractory to treatment or at high risk for recurrence, regardless of disease stage. Methods: Systematic review of the literature. Medline databases (PUBMED), EMBASE and Cochrane Library were consulted, including studies available in full text, published in English, Spanish or Portuguese. Outcomes of interest were overall and progression-free survival. Main Results: The treatment may be feasible and tolerable in patients with high-risk neuroblastoma, however, the benefits of this regimen for survival outcomes are seen only in patients who were in complete response or very good partial response after induction chemotherapy, before the beginning of treatment with 131I-mIBG. Conclusions: There are uncertainties regarding the effectiveness of treatment with 131I-mIBG for increasing the survival of patients diagnosed with neuroblastoma.